2019
DOI: 10.1016/j.resuscitation.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of resuscitative balloon occlusion of the aorta in a swine model of prolonged cardiac arrest

Abstract: Aim-We examined the use of a Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) catheter during cardiopulmonary resuscitation (CPR) after cardiac arrest (CA) to assess its effect on haemodynamics such as coronary perfusion pressure (CPP), common carotid artery blood flow (CCA-flow) and end-tidal CO 2 (PetCO 2) which are associated with increased return of spontaneous circulation (ROSC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…3). It should be considered that CPR itself is a powerful predictor of death, and REBOA is being implemented to buy time for the next treatment in patients with a high risk of death [9,22,23]. Therefore, further research with more accumulated data is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…3). It should be considered that CPR itself is a powerful predictor of death, and REBOA is being implemented to buy time for the next treatment in patients with a high risk of death [9,22,23]. Therefore, further research with more accumulated data is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…REBOA's role is to buy the time to allow for subsequent treatment, such as surgery or angiographic embolization. For patients with a high risk of death [3,23,24], it is very important to implement REBOA accurately and concisely, to reduce the patient's hemorrhagic burden even a little. Many studies have shown that a catheter with a smaller diameter is more favorable for patient safety compared to larger catheters [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Multiple studies have shown thoracic aortic occlusion improves cerebral and coronary perfusion pressures, coronary blood flow, end-tidal carbon dioxide, and overall mortality. 32,[34][35][36][37][38][39] In one notable study of adult swine, during alternating periods of intra-aortic balloon inflation and deflation, balloon inflation increased CPP by an average of 13.7 mmHg (60%) and coronary blood flow increased by 15.5 mL/min (8.5%). 35 placement.…”
Section: Reboa In Animal Non-traumatic Cardiac Arrestmentioning
confidence: 99%
“…32,[34][35][36][37][38][39] In one notable study of adult swine, during alternating periods of intra-aortic balloon inflation and deflation, balloon inflation increased CPP by an average of 13.7 mmHg (60%) and coronary blood flow increased by 15.5 mL/min (8.5%). 35 placement. 41,42 Although Zone 3 occlusion would benefit visceral perfusion and possibly prevent ischemic injury, any hemodynamic benefit was transient or did not translate to improved outcomes.…”
Section: Reboa In Animal Non-traumatic Cardiac Arrestmentioning
confidence: 99%